WORKSHOP DAN PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN DIGITAL DI SDN BUDUG KECAMATAN KWADUNGAN KABUPATEN NGAWI - Mishbahatul Lailiyah Daeng Lala; Rendra Ari Wijaya; Dewi Tryanasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This community service activity was conducted to address the limited digital literacy of teachers and students at SDN Budug, Kwadungan, Ngawi Regency, which impacted the effectiveness of classroom learning. The main objective was to enhance teachers’ skills in designing, creating, and applying digital learning media. A participatory workshop approach was employed, involving all teachers as participants. The activity included preparation and coordination, initial assessment, interactive instruction, practical sessions in developing digital media, and follow-up evaluation. Findings revealed that teachers’ understanding of digital learning media improved after participating in the workshop, as indicated by the comparison between initial and follow-up evaluations. Participants successfully created subject-specific digital materials, such as interactive presentations and basic digital learning resources, suitable for immediate classroom use. Despite demonstrating satisfactory comprehension, further guidance and training are recommended to fully integrate digital media into teaching practices. These results indicate that well-structured workshops and mentoring programs can effectively strengthen teachers’ competencies, foster active learning, and support the development of 21st-century skills for both educators and students.